2015
DOI: 10.7314/apjcp.2015.16.5.1839
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNA-218 and its Clinicopathological and Prognostic Significance in Human Glioma Cases

Abstract: Background: MicroRNAs are a class of noncoding RNAs which regulate multiple cellular processes during tumor development. The purpose of this report is to investigate the clinicopathological and prognostic significance of miR-218 in human gliomas. Materials and Methods: Quantitative RT-PCR (qRT-PCR) was conducted to detect the expression of miR-218 in primary normal human astrocytes, three glioma cell lines and 98 paired glioma and adjacent normal brain tissues.Associations of miR-218 with clinicopathological v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…After further identification and screening individual study, 11 eligible publications underwent full-text review, and 1 article [22] was further excluded because data were unavailable. Finally, we included 10 eligible studies [12,13,2330] in the final evidence synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After further identification and screening individual study, 11 eligible publications underwent full-text review, and 1 article [22] was further excluded because data were unavailable. Finally, we included 10 eligible studies [12,13,2330] in the final evidence synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Among the eligible studies, 10 articles [12,13,2330] evaluated both OS and DFS/PFS/RFS, 6 articles [12,13,23,25,28,30] evaluated DFS/PFS/RFS. Seven studies [12,23,24,2628,30] directly reported HRs and 95% CIs, three studies [13,25,29] reported survival curve (SC).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a number of other types of cancer, miR-218 has been suggested as a prognostic evaluation biomarker; in glioma, low expression of miR-218 was associated with a higher World Health Organization grade and lower Karnofsky scores (20). Furthermore, overexpression of miR-218 in human osteosarcoma Saos-2 cells repressed cell migration and invasion by targeting T-lymphoma invasion and metastasis-inducing protein 1, matrix metalloproteinase (MMP) 2 and MMP9 (21).…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has indicated a critical role of miRNAs in the tumorigenesis and development of different types of cancer including gliomas [6][7][8]. Among them, miR-218 has been reported to be highly downregulated in gliomas compared to normal brain tissues [9][10][11], and decreased expression of miR-218 is strongly associated with poor disease-free survival and overall survival in glioma patients [12].…”
mentioning
confidence: 99%